PENGARUH PEMBERIAN PUPUK NPK ORGANIK TERHADAP PERTUMBUHAN DAN PRODUKSI KEDELAI (Glycine max (L.) Merril) - Eni Marlina; Edison Anom; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Soybean crops are grain-producing potential to be developed and improved production, because of the diversity of its benefits. Soybean production can be enhanced by utilizing the existing land, tilling the soil well and provide fertilizer according to the needs of plants. Organic NPK fertilizer is one of the fertilizer that can be used to increase the production of soybean plants. This research aimed to influence a wide range of organic NPK fertilizer doses and getting the best dose for the growth and yield of soybean. This research has been conducted in the experimental field of the Faculty of Agriculture, University of Riau, Pekanbaru City for 4 months starting in July 2014 to October 2014. This research was carried out experiments using a randomized block design (RBD) with 6 treatments and 4 replications. The treatments used in this research is: ( 350, 400, 450, 500, 550 and 600 ) kg/ha. Data were analyzed statistically using analysis of variance and tested further by using honest significant difference at 5% level. Organic NPK fertilizer significant effect on dry weight of plants, plant height, days to flowering, harvesting, amount pod, amount of pods pithy and production of dry seeds/m2. Organic NPK fertilizer dose administration of 450 kg/ha showed good growth and production of the soybean. Keywords: soybean, organic NPK fertilizer, production